Wing morphology is related to host plants in cactophilic Drosophila gouveai and Drosophila antonietae (Diptera, Drosophilidae) - Soto, I.M. (2008)
A central issue in evolutionary biology is to understand the mechanisms promoting morphological evolution during speciation. In a previous study, we showed that the Neotropical cactophilic sibling species Drosophila gouveai and Drosophila antonietae can be reared in media prepared with their presumptive natural host plants (Pilosocereus machrisis and Cereus hildmaniannus) and that egg to adult viability is not independent of the cactus host. In the present study, we investigate the effects of ecological and genetic factors on interspecific divergence in wing morphology, in relation to the pattern of wing venation and phenotypic plasticity in D. gouveai and D. antonietae, by means of the comparative analysis of isofemale lines reared in the two cactus hosts. The species differed significantly in wing size and shape, although specific differences were mainly localized in a particular portion of the wing. We detected significant variation in form among lines, which was not independent of the breeding cactus, suggesting the presence of genetic variation for phenotypic plasticity and wing shape variation in both species. We discuss the results considering the plausible role of host plant use in the evolutionary history of cactophilic Drosophila inhabiting the arid zones of South America. © 2008 The Linnean Society of London.